Factors Affecting the Size of Platelet Aggregates in Blood - Kennedy, P S; Ware, J; Horak, J K; Solis, R (Thrombosis and Haemostasis, 1981)
Factors affecting the size distribution of platelet aggregates formed in whole blood were measured using an electronic particle counter. Lysis of red cells after dilution of blood for analysis allows detection of smaller aggregates without altering aggregate measurement. Differences in platelet response to increasing concentrations of ADP are detected by an increase in the mean size of platelet aggregates while the total volume of aggregates varies linearly with the volume of available platelets (r = .99). The mean aggregate size varies directly with the total volume of aggregates formed (r = .99). Mean aggregate size is inversely related to the packed red cell volume. As the reactivity of platelets is reduced by incubation with aggregation inhibitors at increasing concentrations, the mean size of aggregates becomes smaller, followed by a decrease in the total volume of aggregates. The total volume and mean size of aggregates formed after incubation with collagen and epinephrine, but not ADP, increases with time after venepuncture.
Keywords: Blood platelets; Platelet aggregation